Avaliação do efeito da eletroestimulação funcional como reabilitação peniana na função erétil de pacientes submetidos à prostatectomia radical - Bispo, Ana Paula dos Santos [UNIFESP] (2018)
Introduction: Erectile dysfunction (ED) after radical prostatectomy is a peculiar form of ED, which preserved with the direct causal event. Objective: To evaluate the effect of functional electrostimulation as a penile rehabilitation procedure on the erectile function of postprostatectomy patients. Methods: This was a prospective, blind, randomized, shamcontrolled trial with 49 patients at the Division of Urology of UNIFESPEPM, through 2014 to 2017. The study included patients undergoing radical prostatectomy with bilateral preservation of the neurovascular bundle, with previous unassisted normal erectile function (International Index of Erectile Function – Erectile Function domain [IIEFEF] score ≥ 26). Patients were undergo functional electrostimulation (FES) or sham procedure. Penile rehabilitation was performed for 6 months, with frequency: 50 Hz; pulse width: 250 microseconds; contraction: 6 seconds; rest: 12 seconds. Patients were evaluated at 1, 3, 6, 9 and 12 months after the start of the procedures. The primary endpoint was proportion of patients with IIEFEF score ≥ 22 after 12 months of the start of treatment. Secondary endpoints included rate of positive responses to Sexual Encounter Profile (SEP) questions 2 and 3 and to Global Assessment Question (GAQ) questions 1 and 2. Results: After 12 months of the start of the study procedures 52.2% and 19.2% of patients reached IIEFEF score ≥ 22 in FES and sham groups, respectively (p = 0,016). A significantly higher proportion of patients in FES group compared to sham group had positive responses to SEP2 and GAQ1 from the 6th month to the end of the study. There was numerical, but no statistical, difference in the rate of SEP3 and GAQ2 positive responses between the groups. Conclusion: Functional electrostimulation was efficacious and safe as a penile rehabilitation procedure in improving recovery of erectile function in patients undergoing radical prostatectomy.